Membangun Kepemimpinan Gereja Yang Berkelanjutan : Menyikapi Tantangan Regenerasi dan Konflik Sinode - Halawa, Yuslina; Ahalapada, Apia; Illu, Jonidius (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to explore the dynamics of leadership regeneration in an ecclesiastical context with an emphasis on three main aspects: the urgency of leadership renewal, the escalation of conflict within the synod, and the contribution of cross-generational participation in the leadership structure. The approach used in this research is descriptive qualitative, which focuses on in-depth understanding of existing phenomena. Regeneration of ecclesiastical leadership is becoming an increasingly urgent issue in the midst of rapid social change, transformation of service orientation, and the declining level of involvement of the younger generation in church organizational structures. In the absence of a structured and sustainable regeneration system, the dominance of certain age groups in leadership may hinder the renewal of the church's vision and the transfer of relevant ministry values. Therefore, leadership regeneration should be viewed as a transformative and contextual structural reform, which aims to respond to the challenges of the times and prepare a more inclusive and adaptive future leadership. Conflicts in church synods are often triggered by the tension between the application of normative church ordinances and the complexity of interpersonal relationships shaped by the history and internal dynamics of the church. Rigid application of ecclesiastical regulations without considering the social context can trigger deliberative dysfunction and polarization, which hinders inclusive decision-making. In this case, managerial skills in managing conflict through dialogic, empathic, and reconciliatory approaches are needed to maintain the cohesion and legitimacy of the synod, so that decisions can reflect the needs and aspirations of the people. Cross-generational participation in church leadership is key to ensuring continuity and synergy in ministry. Collaboration between senior and younger generations can strengthen collective capacity, transform power relations, and create inclusive and sustainable leadership models.